The effect of ripeness level, storage and heating conditions on vitamin C in Fig (Ficus carica L.) fruit juice using bivoltammetry sensor - NERDY NERDY; NILSYA FEBRIKA ZEBUA; TJUT XENA; MAYA KUSUMA; RANI FARAH BUTSAINAH TANJUNG (Universitas Syiah Kuala, 2023)
Vitamin C, as a crucial nutrient, plays a vital role in human health and is known to be sensitive to various factors such as ripeness level, storage and heating conditions. This study aimed to determine the effect of ripeness level, storage and heating conditions on vitamin C in fig (Ficus carica L.) fruit juice using bivolmetric sensor. Fig (Ficus carica L.) fruit juice samples with different ripeness level were collected and analyzed the vitamin C. Full-ripe fig (Ficus carica L.) fruit juice samples subjected at different storage (cold, cool, and room temperature) and heating (30 °C, 60 °C, and 90 °C) conditions. The vitamin C level was monitored using a bivoltammetry sensor. The results showed that the higher ripeness level of fig (Ficus carica L.) fruit the lower level of the vitamin C. The results also showed that the higher storage and heating conditions generally accelerate with degradation of vitamin C. Degradation of vitamin C content in fig (Ficus carica L.) fruit juice with all different storage temperature had the best kinetic model fit zero order. Meanwhile, heating temperature at 30 °C and 60 °C showed that the best kinetic model fit first order. But, heating temperature at 90 °C showed that the best kinetic model fit second order. The kinetic modeling analysis showed that storage and heating conditions significantly influenced the degradation kinetics of vitamin C in the fig (Ficus carica L.) fruit juice.